Separating Spontaneous Symmetry Breaking from Exceptional Points - Hill, Lewis; Gohsrich, Julius; Fauman, Jacob; Ghosh, Alekhya; Kawagoe, Kyle; Del’Haye, Pascal; Kunst, Flore (Nonlinear Photonics, NP 2024 in Proceedings Advanced Photonics Congress 2024 - Part of Optica Advanced Photonics Congress, 2024)
Spontaneous symmetry breaking is often thought of as ubiquitous with an exceptional point. However, we show that for equations describing three different systems from nonlinear optics this is provably not the case.
CRIS-Team Scopus Importer:2025-02-04